Publisher’s Note: Update of Journal Title Abbreviation (Journal of Otorhinolaryngology, Hearing and Balance Medicine, 2026)
Starting 1 September 2026, the Journal of Otorhinolaryngology, Hearing and Balance Medicine will adopt the abbreviation J [...]